An Analysis of Students’ Critical Thinking and Problem Solving Skills in Kinematics: Correlation and Gender Differences - Asep Saefullah; Ida Kaniawati; Ida Hamidah; Nanang Winarno; Atut Reni Septiana (Universitas Syiah Kuala, 2026)
Critical thinking and problem-solving skills are part of the 21st-century competencies students need for future success. This study aims to determine the student profile in both skills, especially in the Kinematics material. This study also measures the correlation between critical thinking and problem-solving skills, as well as the influence of gender differences on both skills. The instrument used in this study was a test consisting of six questions: three to measure critical thinking skills (CTS) and three to measure problem-solving skills (PSS). The study was conducted at a State University in Serang City, Banten Province. The research sample consisted of students from the Physics Education study program, selected using the Convenience Sampling technique, which selects samples based on ease of access or availability. The research sample consisted of students in the physics education study program, selected using the convenience sampling technique, which selects participants based on ease of access or availability. The research sample comprised 72 students, of whom 15 (21%) were males, and 57 (79%) were females. The study's results showed that students' CTS in kinematics averaged 41.67%, indicating very low performance. Meanwhile, PSS were still categorized as low, with an average percentage of 45.84%. Statistical results (p > 0.05) indicated a very weak relationship between CTS and PSS. Meanwhile, the independent-samples t-test showed no significant difference between male and female students on CTS and PSS